Isolating and Identifying Bacteria from Libyan Banknotes in Butchers Shops and Study Sensitivity to Antibiotics and plant Extracts in City Yefren, Libya - Abouzkhar, Farhat Ali Sh. (Sharwes Scientific Journal, 2026)
The study aimed to isolate and identify bacteria associated with Libyan Banknotes currency (the Libyan dinar category), from meat shops in the city of Yefren Libya in March 2020. The results showed that, all the most commonly of the old and new versions traded Banknotes currencies were contaminated with one or more of human pathogenic bacterial species. Four different genera of bacteria which contaminated currency notes were isolated including Klebsiella spp, Staphylococcus aureus, Staphylococcus epidemidis, Corynebacterium spp. and Escherichia coli. The percentage of the bacterial isolates discovered from paper currency notes were different. Biological effectiveness of the alcoholic extract of plants belonging to several plant families ,Eucalyptus torqata, Peganum harmala, Retama raetem, Ephedra spp, Artemisia herba-alba, Rhus tripartite and the aqueous extract of juice of Citrus aurantiifolia on the growth of all bacterial isolates were determined, the results showed that, there was different rates of inhibitory effect of the extracts of Eucalyptus torqata, Rhus tripartite leaves, and Citrus aurantiifoliaof all bacterial isolates. Moreover, this study showed the inhibition rates of plant extracts were increased by percentage of concentrations. The results of efficiency of antibiotics, Ticacillin (75 µg), Cefoxitin (5µg), Kanamycin (30 µg), Rifampicin (5µg), Polymycin (5 µg) and Vancomycin (30µl), in the tested bacterial isolates sowed, different inhibitory effects, however, some plant extracts significantly inhibited the growth of bacterial isolates instead some tested antibiotics.